2020
DOI: 10.3390/jcm9051329
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration Staging by Color Fundus Photography vs. Multimodal Imaging—Epidemiological Implications (The Coimbra Eye Study—Report 6)

Abstract: Epidemiology of age-related macular degeneration (AMD) is based on staging systems relying on color fundus photography (CFP). We aim to compare AMD staging using CFP to multimodal imaging with optical coherence tomography (OCT), infra-red (IR), and fundus autofluorescence (FAF), in a large cohort from the Epidemiologic AMD Coimbra Eye Study. All imaging exams from the participants of this population-based study were classified by a central reading center. CFP images were graded according to the International C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Subjects who participated in the Incidence study also had blood samples collected for genetic analysis. 20 23 We have previously reported on the genetic characterization of this cohort, and we found that rare and low-frequency variants in the CFH gene with damaging effects were more common in AMD cases (Farinha C, et al, unpublished data, 2021). The purpose of this study is to determine the association between the carrier status of rare genetic variants in the CFH gene and the phenotypic features in AMD patients who participated in the Incidence study.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Subjects who participated in the Incidence study also had blood samples collected for genetic analysis. 20 23 We have previously reported on the genetic characterization of this cohort, and we found that rare and low-frequency variants in the CFH gene with damaging effects were more common in AMD cases (Farinha C, et al, unpublished data, 2021). The purpose of this study is to determine the association between the carrier status of rare genetic variants in the CFH gene and the phenotypic features in AMD patients who participated in the Incidence study.…”
mentioning
confidence: 66%
“…Both FAF (488 nm) and IR images were acquired for field 2 at 30° (high resolution with ≥15 frames each). 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a multimodal approach has been recommended to comprehensively visualise AMD and help determine the best clinical management based on structural disease markers 12 . For drusen, several advanced eye imaging modalities such as infrared imaging (IR) 23 , 24 , green scanning laser ophthalmoscopy 25 , fundus autofluorescence (FAF) 26 , 27 and OCT 27 29 have been shown to be useful in differentiating different drusen subtypes 27 , 30 and a multimodal approach is suggested for improved accuracy of AMD staging 31 , 32 . Comparison of drusen segmentation between OCT and en face retinal images also show different advantages to each modality with the former useful for detection of large drusen areas while color fundus photographs (CFPs) are superior in detecting subtle changes in drusen 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The environmental and nutritional risk factors associated with AMD prevalence were previously explored and reported (Cachulo et al, 2016; Raimundo et al, 2018). Subjects who participated in the 6.5‐year follow‐up visit for the estimation of incidence also had blood samples collected for further genetic characterization (Farinha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%